Measuring implosion velocities in experiments and simulations of laser-driven cylindrical implosions on the OMEGA laser. (4th April 2018) - Hansen, E C; Barnak, D H; Betti, R; Campbell, E M; Chang, P-Y; Davies, J R; Glebov, V Yu; Knauer, J P; Peebles, J; Regan, S P; Sefkow, A B
Abstract: Laser-driven magnetized liner inertial fusion (MagLIF) on OMEGA involves cylindrical implosions, a preheat beam, and an applied magnetic field. Initial experiments excluded the preheat beam and magnetic field to better characterize the implosion. X-ray self-emission as measured by framing cameras was used to determine the shell trajectory. The 1D code LILAC was used to model the central region of the implosion, and results were compared to 2D simulations from the HYDRA code. Post-processing of simulation output with SPECT3D and Yorick produced synthetic x-ray images that were used to compare the simulation results with the x-ray framing camera data. Quantitative analysis shows that higher measured neutron yields correlate with higher implosion velocities. The future goal is to further analyze the x-ray images to characterize the uniformity of the implosions and apply these analysis techniques to integrated laser-driven MagLIF shots to better understand the effects of preheat and the magnetic field.